Perceived uncertainty shocks, excess optimism-pessimism, and learning in the business cycle - Chatterjee, Pratiti,Milani, Fabio (CESifo, Center for Economic Studies & Ifo Institute, 2020)
What are the effects of beliefs, sentiment, and uncertainty, over the business cycle? To answer this question, we develop a behavioral New Keynesian macroeconomic model, in which we relax the assumption of rational expectations. Agents are, instead, boundedly rational: they have a finite-planning horizon, and they learn about the economy over time. Moreover, we allow agents to have a potentially asymmetric loss function in forecasting, which creates a direct channel for expected variances to affect the economy. In forming expectations, agents may be subject to shifts in optimism and pessimism (sentiment) and their beliefs may be influenced by their perceptions about future uncertainty. We estimate the behavioral model using Bayesian methods and exploit a large number of subjective expectation series (both point and density forecasts) at different horizons from the Survey of Professional Forecasters. We find that sentiment shocks are the key source of business cycle fluctuations. Shifts in perceived uncertainty can also affect real activity and inflation through a confidence channel, as they play an important role in belief formation. Overall, the results shed light on the importance of behavioral forces over the business cycles, and on the contribution and interaction of first-moment - sentiment - shocks versus second-moment - perceived uncertainty - shocks.
10419/226310
Keywords: Graue Literatur; uncertainty shocks; sentiment; animal spirits; learning; behavioural New Keynesian model; sources of business cycle fluctuations; observed survey expectations; optimism and pessimism in business cycles; probability density forecasts